2018
DOI: 10.2147/cmar.s181742
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 3 as an emerging biomarker in diagnosis and prognosis of hepatocellular carcinoma

Abstract: PurposeHigh mobility group box 3 (HMGB3) is associated with hepatocytes malignant transformation by our previous work. We continued to investigate the diagnostic and prognostic values of HMGB3 for hepatocellular carcinoma (HCC).Patients and methodsCirculating HMGB3 levels were quantitatively detected in a cohort of 225 patients with chronic liver diseases by ELISA and compared with alpha-fetoprotein by the receiver operating characteristic curve. HMGB3 expression in tissues of 170 HCC was detected by tissue mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…160 The concentration of serum HMGB3 is higher in HCC, lower in liver cirrhosis, chronic hepatitis, and the healthy control. 158 The positive expression rate of HMGB3 is higher in the gastric cancer than in the peritumoral tissue. 160 Clearly, HMGB family members are promising diagnostic and prognostic markers in human cancers.…”
Section: Hmgb3mentioning
confidence: 97%
“…160 The concentration of serum HMGB3 is higher in HCC, lower in liver cirrhosis, chronic hepatitis, and the healthy control. 158 The positive expression rate of HMGB3 is higher in the gastric cancer than in the peritumoral tissue. 160 Clearly, HMGB family members are promising diagnostic and prognostic markers in human cancers.…”
Section: Hmgb3mentioning
confidence: 97%
“…We identified a total of 18 studies (Akaike et al, ; Soldevilla et al, ; Chuangui et al, ; Chung et al, ; Cui, Cai, Ding, & Gao, ; W. He et al, ; Gao et al, ; Kwon et al, ; Liu et al, ; Ueda et al, ; Peng et al, ; Rhead et al, ; Kang, Zhang, Zeh, Lotze, & Tang, ; Takeda et al, ; Wittwer et al, ; Xiao et al, ; Yao et al, ; Zheng et al, ) from public databases (PubMed, Web of Science, EMBASE, and Cochrane). The meta‐analysis results indicated that the pooled hazard ratios (HR) were 1.90 (95% confidence interval [CI] = 1.30−2.78) for the high versus low HMGB1, HMGB2, and HMGB3 expression groups ( p < .0001; Figure a) in GC.…”
Section: Resultsmentioning
confidence: 99%
“…The HMGB2 family is 85% similar to the HMGB1 family, with different biological functions in cells (Polanská, Dobšáková, Dvořáčková, Fajkus, & Štros, ); and (c) HMGB3, a member of the high mobility subfamily of the X‐linked HMG proteins that is up to 80% homologous with HMGB1 and HMGB2 (Nemeth, ). An increasing number of studies have reported that HMGB1, HMGB2, and HMGB3 play an important role in several cancers, including hepatocellular carcinoma (Kwon et al, ; Liu et al, ; Xiao et al, ; Zheng et al, ), pancreatic cancer (Chung et al, ; Takeda et al, ; Wittwer et al, ), colon cancer (Soldevilla et al, ; Ueda et al, ; Peng et al, ; Yao et al, ), and esophageal squamous cell carcinoma (Chuangui, Peng, & Zhentao, ; Gao et al, ). However, the role of HMGB1, HMGB2, and HMGB3 expression in GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…HCC [9] and ESCC [10]. Researches also highlighted the role of HMGB3 in proliferation [11], metastasis [12], hypoxia [13] and drug resistance [14].…”
Section: Discussionmentioning
confidence: 99%